Innovative Teaching and Knowledge Economy in Universities from the Perspective of Academics at Mascara University - Mekki Mekkaoui; Soraya Bidi aissaoui; Tayyib Kouadri henni (Journal of North African Economies, 2025)
The purpose of this study is to find out the underlying relationship between the quality of innovative teaching and Knowledge Economy from the perspective of the teachers interviewed in the Faculties at Mascara University. Thus, the study was conducted based on a questionnaire composed of four main axes and the target sample included 120 academics. Then, the questionnaire data were analyzed by using the Statistical Package for the Social Sciences Software (SPSS) based on the calculation of the average scores and the Pearson correlation coefficient. The study concluded that there is a close correlation between the quality of lectures, teaching, and the availability of the requirements of the Knowledge Economy and encouraging research resources and administrative facilities.